A Polyketide Synthase Acyltransferase Domain Structure Suggests a Recognition Mechanism for Its Hydroxymalonyl-Acyl Carrier Protein Substrate - Park, Hyunjun; Kevany, Brian M.; Dyer, David H.; Thomas, Michael G.; Forest, Katrina T. (PLOS ONE, 2014)
We have previously shown that the acyl transferase domain of ZmaA (ZmaA-AT) is involved in the biosynthesis of the aminopolyol polyketide/nonribosomal peptide hybrid molecule zwittermicin A from cereus UW85, and that it specifically recognizes the precursor hydroxymalonyl-acyl carrier protein (ACP) and transfers the hydroxymalonyl extender unit to a downstream second ACP via a transacylated AT domain intermediate. We now present the X-ray crystal structure of ZmaA-AT at a resolution of 1.7 Å. The structure shows a patch of solvent-exposed hydrophobic residues in the area where the AT is proposed to interact with the precursor ACP. We addressed the significance of the AT/ACP interaction in precursor specificity of the AT by testing whether malonyl- or methylmalonyl-ACP can be recognized by ZmaA-AT. We found that the ACP itself biases extender unit selection. Until now, structural information for ATs has been limited to ATs specific for the CoA-linked precursors malonyl-CoA and (2S)-methylmalonyl-CoA. This work contributes to polyketide synthase engineering efforts by expanding our knowledge of AT/substrate interactions with the structure of an AT domain that recognizes an ACP-linked substrate, the rare hydroxymalonate. Our structure suggests a model in which ACP interaction with a hydrophobic motif promotes secondary structure formation at the binding site, and opening of the adjacent substrate pocket lid to allow extender unit binding in the AT active site.